A PENDEKATAN TEORI PESTALOZZI DALAM TERHADAP PENGEMBANGAN KARAKTER ANAK SEKOLAH DASAR: PENDEKATAN TEORI PESTALOZZI DALAM TERHADAP PENGEMBANGAN KARAKTER ANAK SEKOLAH DASAR - Salam, Dudung Abdu; Rukiyati, Rukiyati (CV. Media Publikasi Profesional, 2025)
Character education in elementary schools faces complex challenges in integrating moral values with 21st-century competency requirements. This article aims to reconstruct character education models through a synergy between Johann Heinrich Pestalozzi’s educational philosophy and the Pancasila Student Profile framework. Employing a literature review with a philosophical analysis approach, this research explores the